2008
DOI: 10.1590/s0102-33062008000300015
|View full text |Cite
|
Sign up to set email alerts
|

Palinologia de espécies de Solanum L. (Solanaceae A. Juss.) ocorrentes nas restingas do Estado do Rio de Janeiro, Brasil

Abstract: Foram estudados 21 táxons de Solanum L., com o objetivo de caracterizá-los palinologicamente e, assim, contribuir para a elaboração de um catálogo polínico da flora das restingas do Estado do Rio de Janeiro. Os táxons examinados foram Solanum affine Sendtn., Solanum americanum Mill. var. americanum,Solanum argenteum Dunal ex Poir., Solanum aturense Dunal, Solanum caavurana Vell., Solanum capsicoides All., Solanum carautae Carv., Solanum cordifolium Dunal, Solanum curvispinum Dunal, Solanum echidnaeforme Dunal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…Solanum species had their pollen grains previously studied by Erdtman (1952), Murry & Eshbaugh (1971), Chung & Huang (1972), Salgado-Labouriau (1973), Rao & Ling (1974), Punt & Monna-Brands (1977), Edmonds (1984), Roubik & Moreno (1991), Velásquez & Rangel (1995), Knapp et al (1998), Melhem et al (2003), Al-Quran (2004), Perveen & Qaiser (2007), Batista-Franklim & Gonçalves-Esteves (2008), Barth & Duarte (2008), Cruz-Barros et al (2011), Lashin (2011), Silva et al (2014, Kumar et al (2015), Silva et al (2016), Du et al (2017) and Lorente et al (2017). The authors, in general, describe pollen grains as: monad; isopolar; small to medium size; oblatespheroidal to subprolate shape; circular to triangular and lobate amb; mostly 3-colporate, occasionally 4-colporate, sometimes 2-6 colporate or pantocolporate, syncolporate or parasyncolporate, colpus very long, long or short, with or without margo, fastigium, operculum, granulate or tuberculate colpus membrane and medium constriction; lalongate endoaperture, sometimes elliptic, with or without medium constriction, occasionally forming constinuous ring, with or without margo, costa and fastigium; granulate, granulate-perforate, granulate-punctate, granulatepunctate-fossulate; granulate-verrucate-punctate, echinate, microechinate, microreticulate, psilate, spinulose, spinuloseperforate, spinulose-punctate, reticulate, rugulate-ganulate, scabrate, verrucate, verrucate-punctate, with or without ornamented operculum and aspis; sexine thicker or thinner than nexine or as thick as nexine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solanum species had their pollen grains previously studied by Erdtman (1952), Murry & Eshbaugh (1971), Chung & Huang (1972), Salgado-Labouriau (1973), Rao & Ling (1974), Punt & Monna-Brands (1977), Edmonds (1984), Roubik & Moreno (1991), Velásquez & Rangel (1995), Knapp et al (1998), Melhem et al (2003), Al-Quran (2004), Perveen & Qaiser (2007), Batista-Franklim & Gonçalves-Esteves (2008), Barth & Duarte (2008), Cruz-Barros et al (2011), Lashin (2011), Silva et al (2014, Kumar et al (2015), Silva et al (2016), Du et al (2017) and Lorente et al (2017). The authors, in general, describe pollen grains as: monad; isopolar; small to medium size; oblatespheroidal to subprolate shape; circular to triangular and lobate amb; mostly 3-colporate, occasionally 4-colporate, sometimes 2-6 colporate or pantocolporate, syncolporate or parasyncolporate, colpus very long, long or short, with or without margo, fastigium, operculum, granulate or tuberculate colpus membrane and medium constriction; lalongate endoaperture, sometimes elliptic, with or without medium constriction, occasionally forming constinuous ring, with or without margo, costa and fastigium; granulate, granulate-perforate, granulate-punctate, granulatepunctate-fossulate; granulate-verrucate-punctate, echinate, microechinate, microreticulate, psilate, spinulose, spinuloseperforate, spinulose-punctate, reticulate, rugulate-ganulate, scabrate, verrucate, verrucate-punctate, with or without ornamented operculum and aspis; sexine thicker or thinner than nexine or as thick as nexine.…”
Section: Discussionmentioning
confidence: 99%
“…The pollen morphology of various genera and species of Solanaceae has been described by different types of studies: Pollen morphology of the family in general (Guang-Fang et al 1985;Bernadello & Luján 1997;Khatamsaz & Zangirian 1998;Batista-Franklim & Gonçalves-Esteves 2002;Rojas & Laportte 2004;Rodrigues et al 2016;Dhanya & Devipriya 2016); Pollen morphology of Cestrum or Solanum (Murry & Eshbaugh 1971;Silva et al 2003;Al-Quran 2004;Perveen & Qaiser 2007;Batista-Franklim & Gonçalves-Esteves 2008;Lashin 2011;Kumar et al 2015;Vignoli-Silva et al 2015;Song et al 2018) and Pollen flora of some species (Erdtman 1952;Chung & Huang 1972;Salgado-Labouriau 1973;Rao & Ling 1974;Punt & Monna-Brands 1977;Roubik & Moreno 1991;Velásquez & Rangel 1995;Melhem et al 2003;Barth & Duarte 2008;Cruz-Barros et al 2011;Mercado-Gómez et al 2013;Silva et al 2014Silva et al , 2016Lorente et al 2017). These authors have observed the differences regarding pollen grain aperture and ornamentation of the exine, concluding that the family is eurypalynous.…”
Section: Introductionmentioning
confidence: 99%
“…Solanum L. (Figura 6 R) -Grão de pólen pequeno, isopolar, prolato esferoidal a subprolato; 3-colporado; superfície psilada. Longicolpado; endoaberturas lalongadas quase unidas (Barth & Duarte, 2008;Batista-Franklim & Gonçalves-Esteves, 2008). Dados ecológicos: hábito herbáceo, arbustivo, subarbustivo, arbóreo ou como liana; florestas pluviais e estacionais, áreas antrópicas, campos cerrado, caatinga, restinga, sobre afloramentos rochosos ou como vegetação aquática (Flora do Brasil 2020).…”
Section: Família Solanaceae Ajussunclassified
“…No tocante ao conhecimento palinológico sobre as restingas brasileiras, a maior parte dos estudos publicados se concentram nas regiões sul e sudeste, resultantes de trabalhos de Mendonça e Gonçalves-Esteves (2000), Moreira et al (2004), Souza et al (2004), Gimenes (2007), Gonçalves-Esteves et al (2007), Macedo et al (2007), Gonçalves-Esteves e Batista-Franklin (2008), Lucas et al (2010), Freitas e Carvalho (2012) e Schoroder et al (2019. Por outro lado, a última contribuição para o conhecimento da morfologia polínica de espécies de restingas nordestinas foi feita há mais de três décadas, por Miranda e Andrade (1990), que descreveram algumas espécies ocorrentes no litoral do Ceará.…”
Section: Introductionunclassified